Three Premodern Concepts of Disease : Tri predmoderna koncepta bolesti - Raguž, Marija (Array, 2021)
The concepts of health and disease have an impact on the efficiency of the medical system. Currently, there are no unanimously accepted definitions of health and disease, despite the fact that many investigations have attempted to capture their essence. Most of the available research about the concept of disease relies on the evidence-based disease concept of the modern medicine. That concept differs from the lay concept of disease or illness. In this research we use the cognitive linguistic approach to concepts, taking into consideration the way in which human mind processes the surrounding reality. Those processes are based on the universal principles because of the embodiment of cognition. Consequently, concepts are to some extent independent of time and culture. We have selected three premodern sources with sufficient information about disease to ascertain whether they have similarities in the comprehension of the disease. The first source is "Huangdi Neijing" "Suwen" part, from Chinese ancient medicine, the second one is "Hippocratic Corpus" from ancient Greece, and the third is "Otok" by Josip Lovretić from 19th century eastern Croatia. They are products of very different cultures and historical periods. Conducting comparison of features related to disease in the three sources, we have recognized that body, change, process and control are related to the common shared attributes critical for the concept of disease.